2011
DOI: 10.1152/ajpheart.00405.2011
|View full text |Cite
|
Sign up to set email alerts
|

Short-term oral progesterone administration antagonizes the effect of transdermal estradiol on endothelium-dependent vasodilation in young healthy women

Abstract: Miner JA, Martini ER, Smith MM, Brunt VE, Kaplan PF, Halliwill JR, Minson CT. Short-term oral progesterone administration antagonizes the effect of transdermal estradiol on endotheliumdependent vasodilation in young healthy women. Am J Physiol Heart Circ Physiol 301: H1716 -H1722, 2011. First published August 19, 2011; doi:10.1152/ajpheart.00405.2011.-Very few studies have explored the cardiovascular effects of progesterone in premenopausal women. This study aimed to examine the short-term effects of oral prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 54 publications
4
29
0
1
Order By: Relevance
“…47 For example, physiological concentrations of progesterone can oppose estrogen’s vasodilating effects on the endothelium when measured via flow-mediated dilation. 48 It is important to note that synthetic progestins not only have activity at the progesterone receptor but also at other steroid receptors to have androgenic, glucocorticoid, antiandrogenic, and antimineralocorticoid effects. A progestin’s influence on blood pressure regulation will be highly dependent on its composition and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…47 For example, physiological concentrations of progesterone can oppose estrogen’s vasodilating effects on the endothelium when measured via flow-mediated dilation. 48 It is important to note that synthetic progestins not only have activity at the progesterone receptor but also at other steroid receptors to have androgenic, glucocorticoid, antiandrogenic, and antimineralocorticoid effects. A progestin’s influence on blood pressure regulation will be highly dependent on its composition and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, given the common link between female sex hormones and greater NOS expression in both skeletal muscle and endothelium (Fadel et al 2003; Gavin et al 2009). Estradiol levels increase through the luteal phase and increasing levels of estrogen may create a NOS-mediated rise in exercise vasodilation, although progesterone may offset estrogen-mediated enhancements (Miner et al 2011). Similarly to Parker et al (2007) we studied women in days 1–5 of the menstrual cycle, to minimize sex differences in hormones.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that larger sex differences in exercise vascular conductance could be observed during the luteal phase that are NOS or COX mediated. However, progesterone can counter many vascular effects of estrogen in humans (Miner et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Our current finding that baroreceptor sensitivity remains intact during the ML phase supports the notion that the increase in MSNA during the high hormone phase may be in response to an increase in estrogen-mediated vasodilation. Miner and colleagues (26) recently reported that the addition of exogenous progesterone to exogenous estrogen antagonized flow-mediated vasodilatation in the presence of exogenous estrogen alone. Such differences may potentially explain the lack of increase in SNA during the high hormone (high exogenous estrogen and progesterone) phase in OCP users.…”
Section: Discussionmentioning
confidence: 99%